2003
DOI: 10.1167/iovs.02-0285
|View full text |Cite
|
Sign up to set email alerts
|

Female Gender, Estrogen Loss, and Sub-RPE Deposit Formation in Aged Mice

Abstract: Female gender in aged mice and estrogen deficiency in middle-aged mice appears to increase the severity of sub-RPE deposit formation. Estrogen deficiency may increase susceptibility to formation of sub-RPE deposits by dysregulating turnover of BrM, contributing to collagenous thickening and endothelial changes. Estrogen supplementation at the dosages used in this study does not appear to protect against formation of sub-RPE deposits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 37 publications
3
47
0
1
Order By: Relevance
“…We also reported that aged female or ovariectomized estrogen deficient B6 mice were more susceptible to sub-retinal deposits than males most likely due to dysregulation in matrix turnover (Cousins et al, 2003). In addition, in vitro E 2 administration increased human RPE cell MMP-2 activity (Marin-Castano et al, 2003).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…We also reported that aged female or ovariectomized estrogen deficient B6 mice were more susceptible to sub-retinal deposits than males most likely due to dysregulation in matrix turnover (Cousins et al, 2003). In addition, in vitro E 2 administration increased human RPE cell MMP-2 activity (Marin-Castano et al, 2003).…”
Section: Discussionmentioning
confidence: 71%
“…As described for ARPE-19 cells this treatment provides a non-lethal injury as assessed by cell number and a viability assay (Marin-Castano et al, 2005) MMP-2 and TIMP-2 Activity RPE cell supernatants were collected and the protein concentration of the corresponding cell layer determined. MMP-2 activity was assessed with 10% zymogram gels (Invitrogen Corp., Carlsbad, CA), and TIMP-2 activity with reverse zymography gels as described previously (Cousins et al, 2003). In addition, MMP-2 and TIMP-2 were measured using the human Biotrak activity assay which recognizes mouse MMP-2 or TIMP-2 respectively and normalized to cell number (Amersham Biosciences, Piscataway, NJ).…”
Section: Oxidant Injurymentioning
confidence: 99%
“…194 A lack of oestrogen was shown to be associated with an increase in basal laminar deposits and thickened Bruch's membranes in mice retinae. 197 The authors postulated that oestrogen downregulated matrix metalloproteinase-2, which is 155 or reported by others. 78, 92 The mechanisms for any association between diabetes and ARMD are unknown.…”
Section: Hormonesmentioning
confidence: 81%
“…Mouse (Mus musculus) 0.097 (Cousins et al 2003) 0.036 (Cousins et al 2003) −2.7 5 (Belisle et al 1990) 39 (Belisle et al 1990) 7.8 2 (Belisle et al 1990) 13 (Belisle et al 1990) 6.5…”
Section: Between Species Analysismentioning
confidence: 99%